Paradigma Sufistik Tafsir Al-Qur'an Bedi'uzzaman Said Nursi dan Fethullah Gulen - Ah. Fawaid (SUHUF, 2015)
The article is about to describe the esoteric interpretation of Said Nursi and Fethullah Gulen, its similarities and differences. By using the theory of the social history of interpretation's thought, this paper reveals that neither Nursi nor Gulen alike use the esoteric paradigm in the interpretation of the Qur'an. Esoteric paradigm in Quranic interpretation become an effective strategy used those who live in secular milieu, so they are looking for 'cool atmosphere' in disseminating the Qur'anic to the community who are being attacked by Western civilization and the secular system. Esoteric paradigm in Qur'anic interpretation developed by Nursi and Gulen not absolutely reduces the rule of 'aql besides of qalb and ruh. All three (aql, qalb, and ruh) are used in a balanced way in wading through the ocean of the Qur'an. Besides, Nursi and Gulen refute what Goldziher said that Sufism is the foreign doctrine in Islamic tradition. The Qur'anic interpretation developed by Nursi and Gulen seems more populist interpretation rather than academic debate.